Implementasi Undang-Undang Perkawinan Tentang Pernikahan Dini di KUA Bangkalan Madura - Riza Siptia Wulandari; Muhammad Hipni (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
since Law Number 16 of 2019 concerning Marriage was enacted in Indonesia. However, its implementation in the Bangkalan district community has been ongoing, especially with regard to laws governing marriage registration and the minimum age of marriage. Cultural, educational, economic, and religious factors are one of the causes of the large number of early marriages in Bangkalan Regency that are still taking place below the predetermined minimum age of marriage, which is 19 years for men and 19 years for women. This research uses qualitative research methods, utilizing primary and secondary data sources, document studies and interviews as data collection approaches. Descriptive analytical techniques are used for data analysis. The study aimed to ascertain the extent to which the Office of Religious Affairs has suppressed the rise in early marriage. The impact of this problem will be examined in a number of research issues, including the role of the Office of Religious Affairs in minimizing early marriage in Bangkalan Regency and its consequences. Therefore, the Office of Religious Affairs (KUA) plays a role in reducing cases of early marriage by paying attention to all requirements that must be met by prospective brides, holding weddings, and socializing with the community through counseling and guidance to increase knowledge and understanding of marriage law.